2021
DOI: 10.21203/rs.3.rs-285566/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The 2018 phreatic eruption at Mt. Motoshirane of Kusatsu–Shirane volcano, Japan: Eruption and intrusion of hydrothermal fluid observed by a borehole tiltmeter network

Abstract: We estimate the mass and energy budgets for the 2018 phreatic eruption of Mt. Motoshirane on Kusatsu–Shirane volcano, Japan, based on data obtained from a network of eight tiltmeters and weather radar echoes. The tilt records can be explained by a subvertical crack model. Small craters that were formed by previous eruptions are aligned WNW–ESE, which is consistent with the crack azimuth modeled in this study. The direction of maximum compressive stress in this region is horizontal and oriented WNW–ESE, allowin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The synchronous responses may reflect that both fumaroles are connected to the hydrothermal fluid reservoir that caused the phreatic eruption at Mt. Motoshirane 21 . This is consistent with a magnetotelluric study 23 that suggested the presence of a hydrothermal fluid reservoir (the C2 conductor in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The synchronous responses may reflect that both fumaroles are connected to the hydrothermal fluid reservoir that caused the phreatic eruption at Mt. Motoshirane 21 . This is consistent with a magnetotelluric study 23 that suggested the presence of a hydrothermal fluid reservoir (the C2 conductor in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2 c). The enhanced volcanic activity may reflect the supply of magmatic fluid from a magma chamber, a potential pressure source for deep inflation at a depth of ~ 4 km since 2018 21 , 26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Volcanic tremors were recorded for 8 min beginning at 09:59 (Yamada et al 2021). According to the record of the change in the tilt (Terada et al 2021), the area around the MPCG uplifted from 10:00 to 10:02 and subsided from 10:02 to 10:10, suggesting that the subsidence was due to the release of eruption products. Skiers near the gondola station saw a black vertically elongated jet that spouted from the western foot of the Kagamiike-kita Pyroclastic Cone (Sankei News 2018).…”
Section: Outline Of the Geology Of The Motoshirane Pyroclastic Cone G...mentioning
confidence: 99%